2015
DOI: 10.1002/rcm.7429
|View full text |Cite
|
Sign up to set email alerts
|

Software‐aided cytochrome P450 reaction phenotyping and kinetic analysis in early drug discovery

Abstract: This largely automated workflow enabled the efficient analysis of HRMS data, allowing rapid evaluation of the involvement of the main CYP450 enzymes in the metabolism of new molecules during drug discovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
(80 reference statements)
0
4
0
1
Order By: Relevance
“…Monitoring metabolic stability by a kinetic approach allows not only the half-life calculation for the substrate but also reduction in false positives in the characterization of metabolites. Samples for each time point were analyzed by LC–MS/MS, and raw data were analyzed using Mass-MetaSite software , in the WebMetabase platform. Figure C shows that the PBS/ACN-DMSO protocol significantly increases the stability of 1 ( dBet1 ) during analysis. Therefore, the final method for the metabolic stability assay used in this study included the PBS/ACN-DMSO protocol (see the Methods section for the whole procedure), to reduce the risk of further degradation of the substrate in the autosampler during analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monitoring metabolic stability by a kinetic approach allows not only the half-life calculation for the substrate but also reduction in false positives in the characterization of metabolites. Samples for each time point were analyzed by LC–MS/MS, and raw data were analyzed using Mass-MetaSite software , in the WebMetabase platform. Figure C shows that the PBS/ACN-DMSO protocol significantly increases the stability of 1 ( dBet1 ) during analysis. Therefore, the final method for the metabolic stability assay used in this study included the PBS/ACN-DMSO protocol (see the Methods section for the whole procedure), to reduce the risk of further degradation of the substrate in the autosampler during analysis.…”
Section: Resultsmentioning
confidence: 99%
“…To a solution of 45 (0.100 g, 0.248 mmol) in ACN (3.0 mL), K 2 CO 3 (0.086 g, 0.620 mmol), KI (0.021 g, 0.124 mmol), and propargyl bromide solution (80 wt.% in toluene) (0.031 g, 0.258 mmol) were added, and the mixture was refluxed for 4 h. Then, the solvent was evaporated to dryness and the crude residue was diluted with water, yielding a solid, which was collected by filtration, tritured by DEE, and filtered off to afford the title compound as a yellow-orange solid (0.069 g, 69% yield). 1 4-(4-Fluoro-3-(4-(hex-5-ynoyl)piperazine-1-carbonyl)benzyl)phthalazin-1(2H)-one (68). Under a nitrogen atmosphere, a solution of 45 (0.150 g, 0.372 mmol), 5-hexynoic acid (0.042 g, 0.372 mmol), HBTU (0.175 g, 0.465 mmol), and Et 3 N (0.1 mL, 0.744 mmol) in dry DMF (2.0 mL) was stirred at room temperature for 2 h. Then, the reaction mixture was poured in ice-water and extracted with EA (×3).…”
Section: -((3-chlorophenylmentioning
confidence: 99%
“…Given data sets that span the metabolic capabilities of E. coli , the proposed machine-learning inspired parameterization strategy demonstrated that it is indeed possible to train a single model to predict the genetic and environmentally perturbed phenotypes with fidelity. In the same spirit, the same multi-data set parameterization concepts can be leveraged for applications of kinetic models in personalized healthcare36, biomarker identification37, drug discovery38 and modelling of microbial communities39.…”
Section: Discussionmentioning
confidence: 99%
“…RapidFire™ MS is fully automated and completes integrated sample purification and MS analysis with reduced sample cycle times [2,19]. In reaction-phenotyping experiments, high-resolution mass spectrometry is able to follow the disappearance of the parent compound and concurrently identify and monitor the formation of metabolites in each enzymatic system being evaluated for the NCE [20].…”
Section: In Vitro Assaysmentioning
confidence: 99%